PENGARUH FINANCIAL KNOWLEDGE DAN RISK TOLERANCE TERHADAP FINANCIAL SATISFACTION NASABAH KANTOR PUSAT PT BANK PEMBANGUNAN DAERAH SUMATERA UTARA - Muham Arif Raihan Lubis; Hernawati Lubis; Suwarno Suwarno (Ensiklopedia Education Review, 2021)
This study aims to determine the effect of financial knowledge and risk tolerance on financial satisfaction at the customers of the Head Office of PT. Bank Pembangunan Daerah Sumatera Utara. This study used a purposive random sampling technique using the Slovin formula which was conducted on 100 samples in 2020. The method used was a questionnaire. The results of this study partially financial knowledge had a positive and insignificant effect to and risk tolerance had a positive and significant influence to financial satisfaction. This study shows the implication that individuals must have a good financial knowledge and a good risk tolerance in order to have a high level of financial satisfaction and an established financial condition.Keywords: Financial Knowledge, Risk Tolerance And Financial Satisfaction.